Prevalence of pain and associated factors in elite swimmers - Martins, L. C. X.; Paiva, J. R.; Freitas, A. C.; Miguel, L. B.; Maia, F. R. C. (Science & Sports, 2014)
Introduction: The main focus of sport sciences has been related to athletic performance. In this context, there are relatively few studies that examined occurrence of pain in higher elite athletes. Summary of facts: Prevalence of pain and related factors in 42 swimmers who participated in world championships was investigated. Self-reported questionnaires were applied. Prevalence among men was 18% and 75% among women. Swimming styles showed association with the onset of pain (p < 0.05). Conclusion: Potential health care is needed and more attention must to be paid to the injury mechanisms in elite swimmers. Issues for future studies were pointed.